The Contribution of Ibn Qayyim al-Jawziyya to Salafi Sufism - Lalu Agus Satriawan (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2022)
This article aims to explore the Ibn Qayyim al-Jawziyya’s original views on Sufism. Ibn Qayyim is regarded as an authority in Salafi circles who reject Sufism as a legitimate representation of Islam, especially its philosophical orientation. This article uses a literature research model to reach the finding that Ibn Qayyim understood Sufism as a moral system and part of the science of Islamic morality. Sufism aims to purify the soul to prepare it for its return to God along the path of love. The basis of Sufism as revised by Ibn Qayyim was the Qur’ān, the Sunnah, the traditions of the companions, the ideas of Ibn Taymiyya, and the teachings words of the early Sufi masters. Ibn Qayyim strongly adhered to the orthodox principles of Islamic scholarship later dubbed as Salafism, especially in terms of prioritizing the shari‘a over reason and rejecting esoteric interpretation (ta’wīl). For Ibn Qayyim, the Sufi philosophers were misled in overly relying on ta’wīl and disregarding the role of reason. His approach to Sufism was to perform an objective evaluation of the Sufi teachings circulating at his time. Instead of joining either side, the side of those who condemned it as unlawful innovation (bid‘a) or the side of those who accepted it uncritically, Ibn Qayyim chose to conduct an extensive review of its ideas and practices, rejecting those elements that he found objectionable and accepting others that he found commendable.